Germinacao de sementes em (Stylosanthes macrocephala M.B. Ferr. et Sousa Costa E.S. capitata vog. in Linnaea) - Carmona, R; Ferguson, John E.; Souza Maia, M. de (1986)
High level of seed dormancy in fresh harvested seeds of S. macrocephala and S. capitata was observed. Several treatments were tested in order to increasing seed germination (loss of dormancy). In the physical methods, the seeds were heated to 60oC for 150 minutes and 4oC for 10 and 14 days. The chemical treatments consisted of soaking the seeds in sulphuric acid (98.08%) for 10, 15 and 20 minutes. The scarification and seed cut in the pod were used as a mechanical treatment. The higher germination was obtained with scarification of the seeds. Scarified seeds were also tested in the presence of KNO3 (0.2%), GA3 (500ppm) and thiourea (0.5 and 1,0%). The most effective treatment for germination and tetrazolium test was thiourea. GA3 containing thiourea increased germination in S. capitata however the seedling growth was affected and the seed pathogens were reduced. Based on this result, the thiourea is suitable for these two species although the concentration needs more studies.